2008
DOI: 10.1159/000161057
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Surface Analysis in Subjective Memory Impairment, Mild Cognitive Impairment and Alzheimer’s Dementia

Abstract: Background/Aims: Alzheimer’s disease (AD) is preceded by prodromal states. To determine the neuroanatomical basis for the relationship among such states, we assessed surface conformations of the hippocampus in AD, mild cognitive impairment (MCI) and subjective memory impairment (SMI). Methods: Hippocampal surfaces were reconstructed three-dimensionally via large-deformation high-dimensional MRI brain mapping in 14 SMI, 15 MCI, 12 AD and 13 controls. The surfaces were divided a priori into lateral, superior and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 45 publications
3
28
0
1
Order By: Relevance
“…Total hippocampal volume was not reduced in that sample; however, 3-dimensional surface analysis revealed a localized volume reduction [23] . Other studies with limited sample size also failed to identify hippocampal volume reduction in SMI [24] .…”
Section: Volume Loss Of the Medial Temporal Lobe Structures In Subjecmentioning
confidence: 65%
“…Total hippocampal volume was not reduced in that sample; however, 3-dimensional surface analysis revealed a localized volume reduction [23] . Other studies with limited sample size also failed to identify hippocampal volume reduction in SMI [24] .…”
Section: Volume Loss Of the Medial Temporal Lobe Structures In Subjecmentioning
confidence: 65%
“…This result is consensual as it is independent from the specific method used: it has been reported using radial atrophy (Frisoni et al, , 2006Scher et al, 2007), large deformation high-dimensional brain mapping (Csernansky et al, 2000;Tang et al, 2014;Tepest et al, 2008;Wang et al, 2006Wang et al, , 2003, spherical harmonics (Gerardin et al, 2009;Lindberg et al, 2012) or a VBM-based analysis (Chételat et al, 2008); see Figure 1 for an illustration. In some studies, abnormalities were also found in medial regions of the surface, mostly corresponding to the (pre)subiculum (Frisoni et al, , 2006Wang et al, 2006) or even in all subfields Chow et al, 2012Chow et al, , 2015.…”
Section: Subfield Imaging In Admentioning
confidence: 71%
“…In their article, Tepest et al (2008) reported a slight inward deformation restricted to CA1 as compared to non-complaining healthy controls. This pattern was qualitatively similar to AD and MCI patients but did not reach the level of significance.…”
Section: Cognitively Intact Individuals At Risk For Admentioning
confidence: 96%
See 1 more Smart Citation
“…Segmentation methods that can consistently and precisely delineate the structural boundaries can potentially generate more meaningful results and better detect the minute changes associated with disease progression. Shape analysis of the hippocampus, a medio-temporal lobe structure known for its involvement in long-term memory, has been applied in numerous studies of schizophrenia (Styner et al, 2004;Wang et al, 2008), Alzheimer's disease (Wang et al, 2003;Thompson et al, 2004;Wang et al, 2006;Apostolova et al, 2006;Tepest et al, 2008;Wang et al, 2009), and temporal lobe epilepsy (Hammers et al, 2007). Thus, improved accuracy and reliability of hippocampal segmentation is a relevant issue for future morphometric studies, if methods are to be eventually used for clinical purposes.…”
Section: Introductionmentioning
confidence: 99%